Development of an ultrasonic shear reflection technique to monitor the crystallization of cocoa butter. (September 2015) - Rigolle, Annelien; Foubert, Imogen; Hettler, Jan; Verboven, Erik; Demuynck, Ruth; Van Den Abeele, Koen
Abstract: The quasi-isothermal crystallization process of cocoa butter was monitored by an ultrasonic shear reflection technique utilizing a custom-built experimental set-up in a temperature controlled environment. To facilitate the interpretation of the measurement results, the propagation of shear waves was first theoretically studied in different configurations of gas, liquid or solid layers with varying thickness for the case of normal incidence, yielding theoretical equations of the shear wave reflection coefficient (swRC) for different layering conditions. The typical experimentally observed pattern of the swRC during quasi-isothermal cocoa butter crystallization was subsequently linked to the theoretical equations. The remarkable oscillatory damped response in the swRC as function of the crystallization time could be explained by constructive and destructive interference of a first reflection at the boundary between a plexiglass delay line and the crystallized cocoa butter and a second reflection occurring at the interface between crystallized and liquid substance. This hypothesis was supported by the excitation frequency dependence of the oscillations. The quality of the fit of the theoretical model to the experimental results was very good and also the reproducibility between different independent measurements was acceptable. Finally, measurements at different temperatures (18 °C and 20 °C) suggested that the technique was able to detect differences in crystallization behavior, as measurements at 18 °C displayed faster oscillations compared to measurements at 20 °C. Moreover, this was also confirmed by the theoretical model, as a higher value of the crystallization rate parameter K, exhibited more rapid oscillations. Highlights: Theoretical study of the propagation of shear waves in different configurations Oscillatory pattern is linked to constructive and destructive interferences. Experimental results could be well fitted by the developed theoretical model. The technique was able to detect differences in crystallization behavior.